Rare Bs→γνν- Decay in Family Nonuniversal Z′ Model - Berin Belma Şirvanlı (Advances in High Energy Physics)
The rare Bs→γνν- decay with polarized photon is studied in the framework of a family nonuniversal Z′ model. The branching ratio and photon polarization asymmetry to the model parameters are calculated and compared with the Standard Model. Deviations from the Standard Model will indicate the presence of new physics.